The Influence of Capital And The Amount Of Savings On The Remaining Business Results (RBR) Before Tax At KSP CU Hatirongga Tiga Lama Branch - Vani Oktasya Damanik; Djuli Sjafei Purba; Liharman Saragih (Program Studi Akuntansi Universitas Simalungun, 2024)
The purpose of this research is to analyze the influence of capital and the amount of savings on the remaining business results at KSP CU Hatirongga Tiga Lama Branch. This research is a quantitative study. The population in this research consists of 36 data points. The sampling method uses the saturation sampling technique where the entire population is made the research sample. The data collection technique was carried out using documentation techniques with secondary data, namely financial reports. Hypothesis testing using multiple linear regression analysis. The results of this study show that both partially and simultaneously, capital and the amount of savings have an impact on the remaining business results